The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.15388/ekon.2014.2.3545
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Corporate Governance on Management Efficiency of Lithuanian State-Owned Enterprises

Abstract: Management efficiency of state-owned enterprises (SOE) is being widely discussed not only in Lithuania, Central Eastern Europe, but also globally (mainly focusing on such countries as China, having state monopoly in most of the industries). Moreover, this topic is interesting to scholars both in the context of public governance reforms and a specific area of public administration. On the other hand, the topic of SOEs management is quite specific due to its duality: firstly, it is an area of public governance w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
(18 reference statements)
0
3
0
1
Order By: Relevance
“…2, Juli 2022 page: 1391-1404| 1399 mempertimbangkan pemangku kepentingan lainnya berdasarkan resource dependence theory, serta stewardship theory (Al-Baidhani, 2014). Sedangkan, hasil pembahasan dari Jurkonis & Petrusauskaitė (2014) menyebutkan bahwa hasil self-assessment CG Badan Usaha Milik Negara (BUMN) positif dalam banyak hal dan menunjukkan keyakinan yang cukup kuat terhadap kualitas manajemen di mata eksekutif BUMN Lithuania. Marie L'Huillier (2014) tidak sepakat dengan arti CG yang didominasi oleh literatur pada saat itu dalam teori agensi.…”
Section: Hasil Dan Pembahasanunclassified
“…2, Juli 2022 page: 1391-1404| 1399 mempertimbangkan pemangku kepentingan lainnya berdasarkan resource dependence theory, serta stewardship theory (Al-Baidhani, 2014). Sedangkan, hasil pembahasan dari Jurkonis & Petrusauskaitė (2014) menyebutkan bahwa hasil self-assessment CG Badan Usaha Milik Negara (BUMN) positif dalam banyak hal dan menunjukkan keyakinan yang cukup kuat terhadap kualitas manajemen di mata eksekutif BUMN Lithuania. Marie L'Huillier (2014) tidak sepakat dengan arti CG yang didominasi oleh literatur pada saat itu dalam teori agensi.…”
Section: Hasil Dan Pembahasanunclassified
“…This subject matter dominates among European researchers. Examples of paper topics are corporate social responsibility and ethical tax corporate governance (Hauptman & Belak, 2015), positive effects of the implementation of corporate governance principles in Lithuanian state-owned enterprises (Jurkonis & Petrusauskaitė, 2014), analysis of key corporate governance factors (Domokos et al, 2016), and implementation of good practises of corporate governance in Romania (Dumitraşcu et al, 2015).…”
Section: Analysis Of Dominant Research Categories (General Approach)mentioning
confidence: 99%
“…Curi, Gedvilas, and Lozano-Vivas (2016) assessed the impacts of corporate governance on the efficiency of commercial SOEs in Lithuania and found that good corporate governance, particularly board quality and strategic planning, enhanced firm efficiency. Jurkonis and Petrusauskaitė (2014) investigated Lithuanian SOEs and found that improved corporate governance practices, particularly board independence, led to better financial performance. Miring'u and Muoria (2011) examined SOEs in Kenya and demonstrated that larger board size and a higher ratio of nonexecutive directors on the board had positive impacts on financial performance.…”
Section: Corporate Governance and Performance Of Soesmentioning
confidence: 99%
“…Moreover, in most cases, those studies did not distinguish between private companies and SOEs in their analysis. A few studies have obtained SOE-specific data from a limited number of countries, such as China (Fan, Wong, and Zhang 2007), Italy (Menozzi, Gutiérrez Urtiaga, and Vannoni 2011), Lithuania (Curi, Gedvilas, and Lozano-Vivas 2016;Jurkonis and Petrusauskaitė 2014), Kenya (Miring'u and Muoria 2011), and countries in the Latin America and Caribbean region (Andrés, Guasch, and Lopéz Azumendi 2011;Andrés, Schwartz, and Guasch 2013).…”
Section: Introductionmentioning
confidence: 99%